Analysis of 4H Silicon Carbide Double Implanted MOSFET using Complementary Error Function Doping Profile in Drift Region for increased Breakdown Voltage and Low Power Dissipation - Sagar (ECED, 2016)
The work carried out here on 4H-Silicon Carbide Double Implanted MOSFET(DIMOSFET) is to understand the performance of the above device related to Power Dissipation and Break-down Voltage for Complementary Error Function doping profile in the drift region. The doping profile which is used here can be obtained by mechanism like Molecular Beam Epitaxy(MBE). This profile helps to increase the breakdown voltage while at the same time reduces the series parasitic resistance at the lower end of the device thereby lowering the power dissipation, all of which has also been successfully observed in theoretical analysis here.
Dissertation
Keywords: 4-H SiC; DI- MOSFET; Low Power Dissipation; High Breakdown voltage